Synthesis of Visible-Light-Activated Yellow Amorphous TiO2 Photocatalyst - Chamnan Randorn; John T. S. Irvine; Peter Robertson (International Journal of Photoenergy)
Visible-light-activated yellow amorphous TiO2 (yam-TiO2) was synthesised by a simple and organic-free precipitation method. TiN, an alternative precursor for TiO2 preparation, was dissolved in hydrogen peroxide under acidic condition (pH∼1) adjusted by nitric acid. The yellow precipitate was obtained after adjusting pH of the resultant red brown solution to 2 with NH4OH. The BET surface area of this sample was 261 m2/g. The visible light photoactivity was evaluated on the basis of the photobleaching of methylene blue (MB) in an aqueous solution by using a 250 W metal halide bulb equipped with UV cutoff filter (λ>420 nm) under aerobic conditions. Yam-TiO2 exhibits an interesting property of being both surface adsorbent and photoactive under visible light. It was assigned to the η2-peroxide, an active intermediate form of the addition of H2O2 into crystallined TiO2 photocatalyst. It can be concluded that an active intermediate form of titanium peroxo species in photocatalytic process can be synthesised and used as a visible-light-driven photocatalyst.